Additional Career Assistance and Educational Outcomes for Students in Lower Track Secondary Schools - Bernd Fitzenberger; Stefanie Licklederer (Institute of Labor Economics (IZA), 2017)
Based on local policy variation, this paper estimates the causal effect of additional career assistance on educational outcomes for students in Lower Track Secondary Schools in Germany. We find mostly insignificant effects of the treatment on average outcomes, which mask quite heterogeneous effects. For those students, who are taking extra coursework to continue education, the grade point average is unaffected and the likelihood of completing a Middle Track Secondary School degree falls. In contrast, educational outcomes improve for students who do not take extra coursework. Hence, the treatment causes a reversal of educational plans after graduation.
Keywords: I20; J24; 330; lower track secondary schools; career guidance; educational upgrading